Competition between N and O: use of diazine N-oxides as a test case for the Marcus theory rationale for ambident reactivity. Issue 35 (28th August 2020) - Sheehy, Kevin J.; Bateman, Lorraine M.; Flosbach, Niko T.; Breugst, Martin; Byrne, Peter A.
Abstract : Marcus theory enables rationalisation and quantification of selectivities in reactions of ambident nucleophiles for which the HSAB principle cannot operate. Abstract : The preferred site of alkylation of diazine N -oxides by representative hard and soft alkylating agents was established conclusively using the 1 H– 15 N HMBC NMR technique in combination with other NMR spectroscopic methods. Alkylation of pyrazine N -oxides (1 and 2 ) occurs preferentially on nitrogen regardless of the alkylating agent employed, while O -methylation of pyrimidine N -oxide (3 ) is favoured in its reaction with MeOTf. As these outcomes cannot be explained in the context of the hard/soft acid/base (HSAB) principle, we have instead turned to Marcus theory to rationalise these results. Marcus intrinsic barriers (Δ G ‡0) and Δr G ° values were calculated at the DLPNO-CCSD(T)/def2-TZVPPD/SMD//M06-2X-D3/6-311+G(d, p)/SMD level of theory for methylation reactions of 1 and 3 by MeI and MeOTf, and used to derive Gibbs energies of activation (Δ G ‡ ) for the processes of N - and O -methylation, respectively. These values, as well as those derived directly from the DFT calculations, closely reproduce the observed experimental N - vs. O -alkylation selectivities for methylation reactions of 1 and 3, indicating that Marcus theory can be used in a semi-quantitative manner to understand how the activation barriers for these reactions are constructed. It was found that N -alkylation of 1 is favoured due to the dominant contribution of Δr G ° to the activation barrier in this case, while O -alkylation of 3 is favoured due to the dominant contribution of the intrinsic barrier (Δ G ‡0) for this process. These results are of profound significance in understanding the outcomes of reactions of ambident reactants in general.